Phytoplanktonic associations: a tool to understanding dominance events in a tropical Brazilian reservoir Associações fitoplanctônicas: uma ferramenta para entendimento de eventos de dominância em um reservatório tropical brasileiro - Ariadne do Nascimento Moura; Maria do Carmo Bittencourt-Oliveira; Ênio Wocyli Dantas; João Dias de Toledo Arruda Neto (Acta Botânica Brasílica, 2007)
The aim of this study was to characterize phytoplankton associations, as well as discuss controlling factors determining algal dominance in a eutrophic tropical reservoir, Mundaú, Pernambuco, Brazil. Water samples were collected during the dry period (January/2005) and the rainy period (June/2005). The samples were collected from both limnetic and littoral regions, and the phytoplankton assemblages identified from current literature after preservation in formaldehyde 4%. At the same time as sampling was done, in situ measurements of water temperature, transparency, dissolved oxygen, and pH were also taken. Total phosphorus, total nitrogen concentration and the Trophic State Index were subsequently determined in the laboratory. Phytoplankton density (ind. L-1) was estimated using an inverted Zeiss microscope. Grouping of the phytoplankton associations was carried out using the Reynolds phytosociological classification. During the dry period, reservoir water showed low dissolved oxygen concentrations, alkaline pH and was relatively turbid compared to the situation during the rainy season. Reservoir water is limited by nitrogen during both seasonal periods. The Trophic State Index is classified as determining eutrophic conditions. Phytoplankton was represented by 70 infrageneric taxa grouped in 16 functional associations, with the majority typical of eutrophic systems. This fact is supported by quantitative analysis, which shows the dominance of S associations comprising exclusively R-strategist cyanobacteria. O objetivo deste estudo foi caracterizar as associações fitoplanctônicas, bem como discutir os fatores controladores determinantes da dominância algal em um reservatório eutrófico, Mundaú, Pernambuco, Brasil. As amostras foram coletadas durante dois períodos sazonais, seco (janeiro/2005) e chuvoso (junho/2005). As amostras foram coletadas nas regiões limnética e litorânea, seguidas pela identificação através de literatura específica, e preservadas com formol a 4%. No mesmo momento das coletas dos dados bióticos, alguns parâmetros abióticos como temperatura e transparência da água, oxigênio dissolvido, pH foram obtidos e, em laboratório, foram determinados o fósforo total, nitrogênio total e o Índice de Estado trófico. Os agrupamentos das associações fitoplanctônicas foram feitos a partir da classificação fitossociológica de Reynolds. O reservatório esteve limitado por nitrogênio em ambos os períodos sazonais. No período seco, este sistema apresentou água pouco oxigenada, pH alcalino e relativa turbidez quando comparado com o período chuvoso. O fitoplâncton foi representado por 70 táxons infragenéricos agrupados em 16 associações, sendo a maioria, típica de ecossistemas eutróficos. Este fato é corroborado pela análise quantitativa, os quais evidenciam a dominância de associações S, constituídas exclusivamente por cianobactérias R- estrategistas.